CAREER DEVELOPMENT IN THE OFFICE OF THE MINISTRY OF RELIGION, BADUNG REGENCY - Anak Agung Sagung Mas Trisna Anita, Gregory Paulus Tahu, I Nengah Sudja (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the effect of career development and work discipline on employee performance through motivation as an intervening variable. This research was conducted at the Office of the Ministry of Religion of Badung Regency. The number of samples taken as many as 58 employees, with the saturated sample method. Data collection was obtained from the results of distributing questionnaires. Data analysis using SEM PLS. The results of this study found that career development has a positive and significant influence on work motivation. Career development has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on work motivation. Work discipline has a positive and significant effect on performance. Work motivation has a positive and significant effect on employee performance. Work motivation has a positive and significant effect in mediating the effect of career development on employee performance. Work motivation has a positive and significant influence in mediating the effect of work discipline on employee performance.